The Issue Management Process Of The Parliamentary News Bureau Of The Indonesian House Of Representatives (DPR RI) In Maintaining Reputation : The TNI Law 2025 Ratification Case - Hiya Rain Nahdhah; Kumala Hayati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The ratification of the TNI law by the DPR RI triggered public opinion and negative sentiment in the media that had the potential to affect the reputation of the institution. This condition demands the strategic role of the Parliamentary News Bureau of the Secretariat General of the House of Representatives in managing issues. This study aims to analyze the implementation of issue management by the Bureau in maintaining the reputation of the institution by using the theory of Issue Management Howard Chase and Barry Jones. This study uses a descriptive qualitative approach with sampling techniques carried out by Purposive Sampling techniques, where data are collected through in-depth interviews with selected informants and internal document searches within the Parliamentary News Bureau of the Secretariat General of the House of Representatives. The results showed that issue management was carried out systematically through the stages of identification, analysis, determination of strategy, action programming, and evaluation. The success can be seen from the decrease in the negative tone of the news related to the TNI Act and the strengthening of the Bureau's role as a supporting system in mitigating institutional image. Despite facing institutional obstacles, the Bureau has initiated measures to strengthen internal communication and preparedness.